REMAJA DAN SEKS PRANIKAH (Kasus di Kecamatan Pringsewu Kabupaten Pringsewu) - Saputri, Natalia Desi; Susetyo, Susetyo (SOCIOLOGIE, 2013)
Behavior among adolescents is often used as a reference to any changes regarding the norms and culture within the community itself. Including even when the media began to highlight the most problems related to human existence as a creature that is always evolving (generative) the issue of sexuality. Type in this study is descriptive, is determined by the technique of determining the sample population proposional.teknik mengguna questionnaire data collection, observation, and literature, and for analyzing the data by using a single table by breaking the data descriptively. The results showed that premarital sex behavior among adolescents is quite alarming, because their behavior among related agencies and their mating has experienced the highest ever at 48%. Teens get information about the behavior of the largest premarital sex through a friend that is equal to 52%. The factors that encourage them to do premarital sex behavior is a source of information, knowledge, intensity of the meeting, the place, the age of puberty, family, and media exposure. There is also the impact of, among others, the impact of the individual and the family, and health.Keywords: Adolescents, premarital sex